DEPENDENCE ON CHEMICAL INDUSTRY PRODUCTS MADE FROM OIL AND GAS – ON THE WAY TO THE ANNIHILATION OF HUMANITY - Szarek, Stanisław (Management and Administration Journal, 2023)
The study presents the consequences of economy’s dependence on chemical industry products made from oil and gas. It is reported that the economy is becoming increasingly dependent on the specified products. Based on the NACE Rev2 classification, the author lists the possible implications for all sectors of the economy of the cutting-off of the supplies of chemical industry products made from oil and gas It is demonstrated that the major consequences of the shortage of such products will be borne by agriculture, health protection, transport, automotive industry and construction. The paper lists the oil and gas processing products which are strategic in terms of the economy. The absence of the products may create a global economic crisis and make human development regress by 250 years.